2023
DOI: 10.3390/mining3020011
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Aspects of Potash Mining: A Case Study of the Verkhnekamskoe Potash Deposit

Abstract: Potash fertilizer production is one of the most important economic activities. Historically, potash mining has had a significant impact on the environment, often with catastrophic consequences. The purpose of this paper is to summarize the results of studies on the environmental impact of potash mining using the example of the Verkhnekamskoe potash deposit. The deposit is located in the central part of the Solikamsk depression in the Pre-Ural foredeep (Perm Krai, Russia). All the main features and problems of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Another important aspect related to the environmental impact of construction and closure of potash mines is given in review [13]. The authors concluded that the most effective measure to reduce the adverse environmental impact of potash mining at the VPMSD is hydraulic backfilling of workedout area.…”
Section: Introductionmentioning
confidence: 99%
“…Another important aspect related to the environmental impact of construction and closure of potash mines is given in review [13]. The authors concluded that the most effective measure to reduce the adverse environmental impact of potash mining at the VPMSD is hydraulic backfilling of workedout area.…”
Section: Introductionmentioning
confidence: 99%
“…The growth of the world population predetermines the development of cities, as well as increases the demand for food products and fertilisers [1,2]. Potash is a raw material to produce inorganic fertilisers, so the extraction of this type of mineral increases every year [3,4]. At present, there is a depletion of potash reserves with relatively favourable positions (shallow depth, sufficient thickness, sufficient thickness of watertight strata, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The considered methods of dust suppression using water are characterized by a high efficacy degree, but they are not suitable for potash mines. This is primarily due to the hygroscopicity of the rocks that forms the productive formation under development [13]. The second reason is the adverse impact of this method of dust suppression on the operation of mining machinery and equipment.…”
Section: Introductionmentioning
confidence: 99%